Direct and indirect effects of an invasive omnivore crayfish on leaf litter decomposition - Carvalho, Francisco André Costa (2016)
Invasive alien species (IAS) can disrupt important ecological functions in aquatic ecosystems; however, many of these effects are not quantified and remain speculative. In this study, we assessed the effects of the invasive crayfish Procambarus clarkii (Girard, 1852) on leaf litter decomposition (a key ecosystem process) and associated invertebrates using laboratory and field manipulative experiments. The crayfish had significant impacts on leaf decomposition due to direct consumption of leaf litter and production of fine particulate organic matter, and indirectly due to consumption of invertebrate shredders. The invertebrate community did not appear to recognize P. clarkii as a predator, at least in the first stages after its introduction in the system; but this situation might change with time. Overall, results suggested that the omnivore invader P. clarkii has the potential to affect detritus-based food webs through consumption of basal resources (leaf litter) and/or consumers. Recognizing that this IAS is widespread in Europe, Asia and Africa, and may attain high density and biomass in aquatic ecosystems, our results are important to develop strategies for improving stream ecosystem functioning and to support management actions aiming to control the invasive omnivore P. clarkii.